2011
DOI: 10.1007/s12011-010-8943-3
|View full text |Cite
|
Sign up to set email alerts
|

Proximate and Elemental Composition of Chamelea gallina from the Southern Coast of the Marmara Sea (Turkey)

Abstract: The venerid clam Chamelea gallina is a popular and economic foodstuff around the Mediterranean countries especially in Italy, Spain, and France. The aim of this study is to evaluate the nutritional quality of striped venus of Southern Marmara. Samples were harvested seasonally at five stations and analyzed to determine meat yield, proximate, and elemental composition. According to the results, meat yield ranged from 20.24% to 29.94%. Means of water, protein, lipid, and ash content were 67%, 10.12%, 2.57%, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 17 publications
1
12
2
Order By: Relevance
“…This value only just exceeds the maximum range concentration for Australian and New Zealand food safety standard in molluscs of 2 mg/kg (Abbott et al 2003) (Table 4). Colakoglu et al (2011) reported that the highest Pb concentrations in the venerid clam from Turkey, Chamelea gallina was 3.24 mg/kg, which was higher than this study. As filter feeders, bivalves are more likely to ingest particulate lead than herbivorous gastropods.…”
Section: Discussioncontrasting
confidence: 81%
See 1 more Smart Citation
“…This value only just exceeds the maximum range concentration for Australian and New Zealand food safety standard in molluscs of 2 mg/kg (Abbott et al 2003) (Table 4). Colakoglu et al (2011) reported that the highest Pb concentrations in the venerid clam from Turkey, Chamelea gallina was 3.24 mg/kg, which was higher than this study. As filter feeders, bivalves are more likely to ingest particulate lead than herbivorous gastropods.…”
Section: Discussioncontrasting
confidence: 81%
“…Colakoglu et al. () reported that the highest Pb concentrations in the venerid clam from Turkey, Chamelea gallina was 3.24 mg/kg, which was higher than this study. As filter feeders, bivalves are more likely to ingest particulate lead than herbivorous gastropods.…”
Section: Discussioncontrasting
confidence: 74%
“…Besides being one of the oldest [7], with ∼100,000 t annual landings, the commercial fishery of this species is also among the largest clam fishery in the Mediterranean Sea, particularly in the inshore waters of northern Adriatic Sea [8]. The high fishing pressure has lead to a strong decline in stock abundance [9] further enhanced by several irregular mortality events.…”
Section: Introductionmentioning
confidence: 99%
“…Lead (Pb), for example, which may causes serious disorders in living organisms, is found in the marine environment at higher levels due to wastes of petroleum industry wastes. However, Cd levels are known to be related to the mining, urbanization and agricultural runoffs containing phosphoric fertilizers 35 . Among these toxic metals, Hg is a naturally occurring toxic metal and generally transforms into methylmercury (MeHg) in the marine environment and accumulates in living organisms 35, 36 .…”
Section: Discussionmentioning
confidence: 99%